THE DYNAMICS OF TRADE AT THE EUROPEAN UNION LEVEL. CASE STUDY – UNITED KINGDOM - Maria-Anca CRAIU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2019)
This paper analyzes the dynamics of trade at EU level, using panel data for the 28 Member States (MS). The relationship between GDP, population level, imports and exports for the period 2010-2017 is analyzed. Afterwords we move to a particular case, namely the United Kingdom using data series for the period 2008 - 2017 and the same variables as above. In this case, the relationship between GDP, exports and population level will be analyzed.In both cases, the data source is Eurostat.